THE INFLUENCE OF SCHOOL PRINCIPALS' MANAGERIAL COMPETENCE AND TRANSFORMATIONAL LEADERSHIP ON THE PERFORMANCE OF STATE PRIMARY SCHOOL TEACHERS - TARJO, Tarjo (Journal of Education and Leadership in Education, 2024)
The aim of this research is to analyze: 1) The direct influence of the principal's managerial competence on the performance of public elementary school teachers in Larangan District, Tangerang City. 2) The direct influence of transformational leadership on the performance of public elementary school teachers in Larangan District, Tangerang City. 3) The direct influence of the principal's managerial competence on the transformational leadership of the Larangan District Public Elementary School, Tangerang City. The method used in this research is a causal survey research method with path analysis techniques. The population in this study were all ASN teachers at public elementary schools in Larangan District, Tangerang City, totaling 135 ASN teachers with a sample of 100 ASN teachers taken at random (proportional random sampling). Based on the results of the analysis, it is proven that: 1) There is a positive and significant direct influence of the principal's managerial competence on the performance of state elementary school teachers in Larangan District, Tangerang City. 2) There is a direct positive and significant influence of the transformational leadership on the performance of public elementary school teachers in Larangan District, Tangerang City. 3) There is a direct positive and significant influence of the principal's managerial competence on the transformational leadership of state elementary school teachers in Larangan District, Tangerang City.